Aborted Tracheo-esophageal Fistula in a Neonate. (September 2018) - Hallett, John M; Bryant, Victoria; Drake, David; George, Simi; Upadhyaya, Manasvi
Esophageal atresia (EA) is an uncommon congenital anomaly which is often associated with a tracheoesophageal fistula. An isolated EA is a rarer anomaly and its diagnosis has implications for the ongoing treatment and outcome of the infant. For the first time, we report a case of a premature newborn with a pure EA and a tracheal diverticulum, containing both respiratory and esophageal mucosa. We have termed this an aborted trachea-esophageal fistula. Recognition of these very rare variations of foregut anomalies may contribute to our understanding of their pathogenesis.